Ouers se Persepsies oor Bullebakkery in ’n Skoolkoshuis: ’n Gevallestudie - de Wet, N. C. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2007)
The impetus for the case study on bullying was the concern of the parents of one of the children about the physical and emotional well-being of their children in an Eastern Cape school hostel. Discussions that the parents had with the hostel superintendent did not lead to the termination of the victimisation by one of their boys. On the contrary, it aggravated the situation. After discussions with the researcher, and with the support of the hostel committee, hostel superintendent and secondary school principal, an in-depth investigation into the nature and extent of bullying at the hostel was undertaken. The research instruments are based on the Delaware Bullying Questionnaire. Parents, staff on duty and learners were involved in the research. In this article the parents’s perceptions with regard to bullying are reported. From the qualitative and quantitative data it is apparent that direct and indirect verbal, as well as physical and emotional harassment are fairly common occurrences in the Eastern Cape hostel. Moreover, it has been found that boys in particular, as well as older children in positions of authority are the aggressors. The parents identified the way to school and back, as well as the hostel bathrooms, playing grounds and hostel bedrooms as relatively unsafe areas. Parents expressed their frustration with the seeming lack of action by the staff on duty. In the article some guidelines for parents are also provided to assist them in protecting their children against bullying.